Knowledge-based system with CommonKADS analysis for school botanical garden - Atichart Harncharnchai (2018)
© 2017 Association for Computing Machinery. This study aims to plan, analyse and develop a knowledge-based system (KBS) that provides problem-solving solution for field operation of the School Botanical Garden, a project under Her Royal Highness Princess Maha Chakri Sirindhorn, to educate and create awareness of plant genetics for juveniles. Existing system mainly provides information about plant information and operating guidelines but lacks knowledge about the domain-specific problem and its solution. The primary data were collected from experts using semi-structured interview to capture knowledge about problem-solving in the field operational tasks. With the CommonKADS methodology, the analysis revealed the system feasibility and problem-related tasks including plant label creation and plant area measurement, representing in a form of knowledge maps. The development of a prototype KBS was also proposed.